Noninvasive in Vivo Imaging of Protein Kinase a Activity - Jan Øivind Moskaug; Harald Carlsen; Rune Blomhoff (Molecular Imaging)
Protein kinases play pivotal roles in almost all cellular signaling pathways, and modulation of their activity is desirable in both disease and studies of function. Information on the activity of kinases in vivo is scarce owing to a lack of appropriate methods. To obtain such information, we produced mice in which protein kinase A (PKA) activity can be monitored noninvasively in vivo. The model uses luciferase, which has been mutated to contain a target sequence of PKA, thus making luminescence from the enzyme dependent on its state of phosphorylation. The PKA-sensitive luciferase, termed luciferase PKA , was incorporated into the mouse genome, and transgenic animals exhibited a rapid β-adrenergic response, that is, reduced luminescence, in various organs, including the pancreas, muscle, liver, and fat, after isoproterenol injection. This study shows that luciferase can be used for in vivo measurements of kinase activity, suggesting that different kinase target sequences in luciferase can monitor kinase activity modulation.